2022
DOI: 10.1002/jmr.2959
|View full text |Cite
|
Sign up to set email alerts
|

Identification of benzothiazole‐rhodanine derivatives as α‐amylase and α‐glucosidase inhibitors: Design, synthesis, in silico, and in vitro analysis

Abstract: A novel series of benzothiazole-rhodanine derivatives (A1-A10) were designed and synthesized, with the aim of developing possible antidiabetic agents and the spectral characterization of these compounds was done using infrared spectroscopy (IR), proton-nuclear magnetic resonance ( 1 H-NMR), carbon-nuclear magnetic resonance (C 13 -NMR), and high resolution mass spectroscopy (HR-MS) techniques. In vitro hypoglycemic potential of the compounds was evaluated by performing α-amylase and α-glucosidase enzyme inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…determined that compounds containing rhodanine benzothiazole are α‐amylase and α‐glucosidase inhibitors. Due to the electron‐donating group (OH) positioned at position‐4, compound 45 has strong inhibitory effects on α‐glucosidase and α‐amylase activity with IC 50 : 24.61±1.76 μM and 24.64±2.10 μM respectively [53] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…determined that compounds containing rhodanine benzothiazole are α‐amylase and α‐glucosidase inhibitors. Due to the electron‐donating group (OH) positioned at position‐4, compound 45 has strong inhibitory effects on α‐glucosidase and α‐amylase activity with IC 50 : 24.61±1.76 μM and 24.64±2.10 μM respectively [53] …”
Section: Discussionmentioning
confidence: 99%
“…Due to the electron-donating group (OH) positioned at position-4, compound 45 has strong inhibitory effects on α-glucosidase and α-amylase activity with IC 50 : 24.61 � 1.76 μM and 24.64 � 2.10 μM respectively. [53] Patil Ser497, and Ser505. [54] RB C et al identified rhodanine benzothiazole compounds as α-amylase and α-glucosidase inhibitors.…”
Section: Pharmacological Characteristics Of Benzothiazole Analoguesmentioning
confidence: 98%
“…Benzothiazole clubbed derivatives of rhodanine 25 a – j were synthesized by Srinivasa and coauthors [82] and evaluated for their antidiabetic potential against α‐amylase and α‐glucosidase enzymes. Compounds 25 e and 25 i displayed comparable inhibitory potential with IC 50 =24.22 and 24.64 μM, respectively, against α‐amylase enzyme with standard Acarbose (IC 50 =24.35 μM), whereas with α‐glucosidase, compounds 25 g and 25 i displayed significant inhibition with IC 50 =24.74 and 24.61 μM, respectively.…”
Section: Thiazolidinone Based α‐Amylase Inhibitorsmentioning
confidence: 99%
“…In case of analog 5 and 6, interactions were found such as vander Waals, conventional hydrogen bond, Pi-anion, Pi-Sigma, alkyl, Pi-alkyl, salt bridge, halogen, Pi-sulphur, etc. The further detail of docking study were summarized as in our previous articles [ 30 , 31 , 32 , 33 , 34 , 35 ] and the assay protocols of both the activities have been added in Supplementary file [ 36 , 37 ].…”
Section: Biological Profilementioning
confidence: 99%